Prevalence and determinants of physical violence against doctors in Bangladeshi tertiary care hospitals - Md. Shahjalal; Mohammad Morshad Alam; Md. Nafiul Alam Khan; Arifa Sultana; Sanjana Zaman; Ahmed Hossain; Mohammad Delwer Hossain Hawlader (Human Resources for Health, 2023)
Abstract Background The increasing physical violence against doctors in the health sector has become an alarming global problem and a key concern for the health system in Bangladesh. This study aimed to determine the prevalence and associated factors of physical violence against doctors in Bangladeshi tertiary care hospitals. Methods A cross-sectional survey was performed among 406 doctors working in tertiary care hospitals. Data were collected using a self-administered questionnaire and the binary logistic regression model was employed for predicting physical violence against doctors. Results Of the participants, 50 (12.3%) doctors reported being exposed to physical violence in 12 months prior to the survey. According to logistic regression analysis, aged less than 30 years or younger, male and never-married doctors were prone to physical violence. Similarly, doctors from public hospitals and those worked in emergency departments were at higher risk of physical violence. More than 70% of victims reported that patients’ relatives were the main perpetrators. Two-thirds of the victims referred to violence in the hospitals as a grave concern. Conclusions Physical violence against doctors is relatively common in the emergency departments and public hospitals in Bangladesh. This study found that male and younger doctors were at high risk of exposing physical violence. To prevent hospital violence, authorities must develop human resources, bolster patient protocol and offer physician training.